Adiponectin as a predictor of mortality and readmission in patients with community-acquired pneumonia: a prospective cohort study - Dungu, Arnold Matovu; Ryrsø, Camilla Koch; Hegelund, Maria Hein; Sejdic, Adin; Jensen, Andreas Vestergaard; Kristensen, Peter Lommer; Krogh-Madsen, Rikke; Faurholt-Jepsen, Daniel; Lindegaard, Birgitte (Frontiers in Medicine, 2024)
Background: Adiponectin is secreted by adipocytes and is inversely associated with obesity. Given the association between low body mass index (BMI) and higher mortality risk after communityacquired pneumonia (CAP), we hypothesised that high adiponectin levels are associated with a higher risk of adverse clinical outcomes in patients with CAP.In a prospective cohort study of 502 patients hospitalised with CAP, adiponectin was measured in serum at admission. The associations between adiponectin and clinical outcomes were estimated with logistic regression analyses adjusted for age, sex, and measures of obesity (BMI, waist circumference or body fat percentage).Results: Adiponectin was associated with higher 90-day mortality for each 1 µg/mL increase (OR 1.02, 95% CI [1.00, 1.04], p = 0.048) independent of age and sex. Likewise, adiponectin was associated with a higher risk of 90-day readmission for each 1 µg/mL increase (OR 1.02, 95% CI [1.01, 1.04], p = 0.007) independent of age and sex. The association between adiponectin and 90day mortality disappeared, while the association with 90-day readmission remained after adjusting for adiposity.Adiponectin was positively associated with mortality and readmission. The association with mortality depended on low body fat, whereas the association with readmission risk was independent of obesity.